Analisis Dinamik Model Predator-Prey dengan Struktur Usia dan Perilaku Anti-Predator - Al Idrus, Ainun Sukmawati; Abd. Gani, Ayub Prianto; Zaid, Nurlaila (Scimadly Publishing, 2022)
This article discusses the Predator-prey Holling type II model involving age structure and anti-predator behaviour. The age structure is given to the predator population, which is divided into two, namely juvenile predators and adult predators, while in the prey population, there is anti-predator behaviour, namely the tendency to defend against predator attacks. The model analysis includes the determination of a fixed point, analysis of the stability of the fixed point and numerical simulation. Three fixed points were obtained, namely the fixed point of population extinction (), the fixed point of predator extinction and the fixed point of population existence. Stability analysis shows that is always a saddle while and are conditionally stable. Furthermore, it is shown that the two conditions are both stable nodes. At the end, a simulation shows that the population dynamics that occur are highly dependent on the initial conditions of the population and the value of the anti-predator behaviour parameter of the prey population.